BWRO DESALINATION FOR POTABLE WATER SUPPLY ENHANCEMENT IN COASTAL REGIONS - I Nyoman Widiasa; Vita Paramita; Heny Kusumayanti (JOURNAL OF COASTAL DEVELOPMENT, 2009)
Most of coastal regions in Indonesia have experienced water scarcity where water resources are becoming more and more threatened due to the rapid growth of population, aquaculture industries and agricultures. Brackish water reverse osmosis (BWRO) desalination may be used to overcome the supply potable water problem in the coastal regions. Brackish water having total dissolved solids (TDS) content in the range of 1,000–10,000 ppm can be desalinated at a reasonable cost. This work was aimed to find valuable technical data for plant design and operation. Cost analysis also was conducted to obtain specific water cost. The results show that stable system performance was achieved. Based on a case study of small scale BWRO with capacity of 50 m3/day, specific water cost was around of IDR 6,100/ m3.